CFD analysis of the hydrodynamic characteristics of an eccentric shaft in a canned motor. Issue 7 (March 2019) - Jia, Zhen; Zuo, Zhigang; Liu, Shuhong
Abstract: Boiler water circulation pump is the core of the 600MW and above supercritical boiler start system and the subcritical boiler furnace forced circulation system. A pressure fluctuation with the same frequency as shaft rotation was found during the use of a boiler water circulation pump at its outlet. Based on an engineering problem, the effects of eccentricity with axial flow on the hydrodynamic characteristics of the Taylor-Couette system is numerically studied in a simplified shaft system of canned motor, by using RNG k-ε turbulence model to solve the near-wall region more accurately. Sliding mesh is used to calculate the hydrodynamic balance of the shaft. Results show that the fluctuation rule of pressure in the entire shaft system is quite consistent. The pressure loss increases along the axial flow, and finally there is no pressure fluctuation at the outlet.